Efficiency of Islamic Banking Compared to Conventional Banking: Evidence from Indonesia Banking Sector - Pradiknas, Tiyo Yoga; Fathurohman, Taufik (Journal of Business and Management, 2015)
Abstract - Islamic banks today have rapid growth around the world. According to Solé (2007), Islamic banks exist not only in the countries that have a majority Muslim population, but also countries where Muslim are not predominant. From Indonesian Banking Statistics data in 2004-2013, Islamic banks have higher LDR than conventional banks. The main issue in this research is whether Islamic banks can maintain their efficiency while they increasing their performance. The hypothesis of this research is the efficiency of Islamic banking is higher and statistically significantly different from conventional banking. This research uses output-oriented VRS DEA model with asset approach to measure efficiency. Then, Mann-Whitney test used to compare the DEA results since the results show non-parametric data. Lastly, Spearman’s correlation will be applied in order to analyze the relationship between loans to deposit ratio with the efficiency of both types of the bank. The DEA and Mann-Whitney test results prove that Islamic banking is significantly different and more efficient than conventional banks in the period of 2004-2013. It proved by DEA results in 2005, 2010, 2011, 2012, and 2013. In these years, Islamic banks are statistically significant more efficient than conventional banks. Then this result was supported by single-multi year efficiency that proved that Islamic banks are significantly different and more efficient than conventional banks. The Spearman’s correlation findings identifies there is significant correlation between LDR and efficiency of both types of bank at significance level 0.01. The Spearman’s correlation coefficient is 0.293, which means there is a weak relationship between LDR and efficiency of both types of the bank. This research’s results can be used as consideration for the government to assign Islamic banks to support real sector since Islamic banks allocate most of their fund to financing (lending) products. Furthermore, intermediary and production approach can be considered to apply in the future research to get better insight. The lack of explanation why Islamic banking is significantly different and more efficient than conventional banking can be a topic of the future research. Keywords: asset approach, Data Envelopment Analysis (DEA), efficiency, Islamic banks